Seasonal distribution and habitat use preference of Barking deer (Muntiacus vaginalis) in Murree-Kotli Sattian-Kahuta National Park, Punjab Pakistan - Habiba,U. (2022)
ABSTRACT Microhabitat factors associated with the habitat of barking deer (Muntiacus vaginalis) were examined and compared between summer and winter seasons. Habitat characteristics and preferred habitat were measured by locating direct and indirect signs. To quantify the habitat utilization of barking deer, each selected study site was sampled for floral diversity from 2015 to 2017. Quadrats were deployed along transect lines to determine seasonal distribution. Barking deer were not evenly distributed across vegetation types in the study area; they occurred more often in the broad-leaved forest than in Chir pine forest, at an elevational range of 550-850 m, in thick vegetation on steep slopes. The most preferred habitat included trees and shrubs with 30% and 69% cover, respectively. Barking deer avoided thicker tree cover, possibly as it hinders movement and escape from predators. No significant difference (χ2 = 6.37, df = 3, p = 0.19) in seasonal vegetation cover was recorded.